Resource‐seeking agglomeration: a study of market entry in the lodging industry - Kalnins, Arturs; Chung, Wilbur (Strategic Management Journal, 2004)
Abstract We analyze whether firms prefer collocating with incumbent firms when choosing among markets to enter, highlighting the role of resource‐seeking as a motivation for collocation. We propose that entrants will locate near others possessing resources that can spill over, but will avoid locations where existing firms will exploit spillovers without contributing. To test these propositions, we analyze the location decisions of 570 new hotels in Texas between 1992 and 2000. We find that hotels are attracted to markets with branded upscale hotels. Further, we find that owners of upscale hotels avoid markets with hotels without similar resources. Copyright © 2004 John Wiley & Sons, Ltd.